Climate-Induced Infertility in Dairy Cows: Pathways, Challenges, and Solutions for Sustainable Dairy Development - Md. Emran Hossain (International Journal of Climate Conditions, 2025)
Climate change has emerged as a significant challenge to dairy production, with profound implications for reproductive performance in dairy cows. The interplay of rising temperatures, fluctuating rainfall patterns, and increased frequency of extreme weather events disrupts key physiological, nutritional, and behavioral processes essential for fertility. Heat stress alters hormonal balance, impairs oocyte and embryo quality, reduces estrus expression, and affects pregnancy outcomes. Concurrently, climate-induced nutritional deficits, immune suppression, and increased prevalence of reproductive diseases exacerbate fertility challenges. This review explores the multifactorial pathways through which climate change impacts fertility in dairy cows, emphasizing physiological mechanisms, environmental stressors, and genetic predispositions. Mitigation strategies such as improved cooling systems, optimized nutrition, genetic selection for heat tolerance, and sustainable reproductive management practices are critically discussed. By integrating current knowledge and identifying research gaps, this review provides actionable insights for safeguarding reproductive efficiency and ensuring sustainable dairy production in the face of climatic adversity.
Keywords: Climate change; Heat Stress; Nutritional Deficits; fertility; reproductive performance